P300 Acetyltransferase Is a Cytoplasm‐to‐Nucleus Shuttle for SMAD2/3 and TAZ Nuclear Transport in Transforming Growth Factor β–Stimulated Hepatic Stellate Cells. Issue 4 (23rd May 2019) - Wang, Yuanguo; Tu, Kangsheng; Liu, Donglian; Guo, Luyang; Chen, Yunru; Li, Qing; Maiers, Jessica L.; Liu, Zhikui; Shah, Vijay H.; Dou, Changwei; Tschumperlin, Daniel; Voneschen, Luke; et al.
Abstract : Nuclear translocation of mothers against decapentaplegic homolog 2/3 (SMAD2/3), core transcription factors of transforming growth factor β (TGF‐β) signaling, is critical for hepatic stellate cell (HSC) differentiation into metastasis‐promoting myofibroblasts. SMAD2/3 have multiple coactivators, including WW domain‐containing transcription regulator protein 1 (WWTR1 or TAZ) and p300 acetyltransferase. In the nucleus, TAZ binds to SMAD2/3 to prevent SMAD2/3 nuclear export. However, how TAZ and SMAD2/3 enter the nucleus remains poorly understood because neither contains a nuclear localization signal (NLS), an amino acid sequence tagging proteins for nuclear transport. p300 is an NLS‐containing large scaffold protein, so we hypothesized that SMAD2/3 and TAZ may undergo nuclear import through complexing with p300. Coimmunoprecipitation, immunofluorescence, and nuclear fractionation assays revealed that TGF‐β1 promoted binding of SMAD2/3 and TAZ to p300 and that p300 inactivation disrupted TGF‐β1‐mediated SMAD2/3 and TAZ nuclear accumulation. Deleting the p300 NLS blocked TGF‐β1‐induced SMAD2/3 and TAZ nuclear transport. Consistently, p300 inactivation suppressed TGF‐β1‐mediated HSC activation and transcription of genes encoding tumor‐promoting factors, such as connective tissue growth factor, Tenascin C, Periostin, platelet‐derived growth factor C, and fibroblast growth factor 2, as revealed by microarray analysis. Chromatin immunoprecipitation‐real‐time quantitative PCR showed that canonical p300‐mediated acetylation of histones also facilitated transcription in response to TGF‐β1 stimulation. Interestingly, although both TGF‐β1‐mediated and stiffness‐mediated HSC activation require p300, comparison of gene expression data sets revealed that transcriptional targets of TGF‐β1 were distinct from those of stiffness‐p300 mechanosignaling. Lastly, in tumor/HSC coinjection and intrasplenic tumor injection models, targeting p300 of activated‐HSC/myofibroblasts by C646, short hairpin RNA, or cre ‐mediated gene disruption reduced tumor and liver metastatic growth in mice. Conclusion: p300 facilitates TGF‐β1‐stimulated HSC activation by both noncanonical (cytoplasm‐to‐nucleus shuttle for SMAD2/3 and TAZ) and canonical (histone acetylation) mechanisms. p300 is an attractive target for inhibiting HSC activation and the prometastatic liver microenvironment.